Harry Potter and personality assessment: The utility of the Sorting Hat Quiz in personality traits’ assessment - Lidia Baran; Maria Flakus; Franciszek Stefanek (PLoS ONE, 2025)
Interactions with fiction influence our behavior and identification, as fiction encompasses elements of day-to-day reality. For instance, Harry Potter (HP) readers often identify with one of the Hogwarts Houses, recognizing their personality traits as similar to one of the house’s members. This tendency constitutes a fertile ground for the popularity of the Sorting Hat Quiz (SHQ), i.e., a quiz allowing a placement to one of the houses. Recent studies showed that SHQ predicts some personality traits, i.e., Big Five, Dark Triad, and need for cognition. However, those studies were focused only on HP fans. Thus, the presented study aimed to replicate and extend previous studies by (1) using more complex measurements of personality traits and (2) analyzing the obtained results in groups of HP readers and non-readers. Our findings suggested that although participants sorted (or desired to be sorted) into a particular house shared some of the hypothesized personality features, the predictive power of the SHQ was limited only to HP readers, with minor or non-existent effects in the non-reader subsample. We discuss the obtained result in light of the narrative collective assimilation hypothesis and offer directions for future studies focused on the culture-based phenomenon.